2007
DOI: 10.4314/thrb.v9i2.14316
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac risk indicess of staff of Federal Univesity of Technology Owerri, Imo state, Nigeria

Abstract: Non-communicable diseases are the major health burden in the industrialized countries and are increasing rapidly in the developing countries owing to demographic transitions and changing lifestyles among the people. Cardiovascular diseases (CVD) are increasingly becoming a great cause of morbidity and mortality. A total of 100 senior and 141 junior staff in Federal University of Technology, Owerri (FUTO), Imo State, Nigeria was randomly selected for a study on cardiac risk factors. A questionnaire was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
7
2
Order By: Relevance
“…[27,28] Emerole et al reported that the cardiac risk indices of staff of Federal University of Technology, Owerri, Nigeria was high especially among the senior staff. [29] The prevalence of CV risk factors in our study was found to be higher than most institutional based study/reports from Nigeria. [27][28][29] It was also higher that reports from the Abia state noncommunicable diseases and CV risk factors survey where the prevalence of hypertension was found to be 31%.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…[27,28] Emerole et al reported that the cardiac risk indices of staff of Federal University of Technology, Owerri, Nigeria was high especially among the senior staff. [29] The prevalence of CV risk factors in our study was found to be higher than most institutional based study/reports from Nigeria. [27][28][29] It was also higher that reports from the Abia state noncommunicable diseases and CV risk factors survey where the prevalence of hypertension was found to be 31%.…”
Section: Discussioncontrasting
confidence: 73%
“…[29] The prevalence of CV risk factors in our study was found to be higher than most institutional based study/reports from Nigeria. [27][28][29] It was also higher that reports from the Abia state noncommunicable diseases and CV risk factors survey where the prevalence of hypertension was found to be 31%. [28] This and many similar studies therefore suggest a rapid epidemiologic transition to the high prevalence of noncommunicable diseases (often preceded by CV risk factors) in the nearest future in Nigerian Universities and the need to institute preventive programs to reduce the burden.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, the prevalence of high cardiovascular risk is equally lower than what was reported by Emerole in the tertiary institutions in Nigeria [44]. This lower prevalence could probably result from low socioeconomic status of the respondents compared with what obtains in the university settings, since poverty has been found to be associated with a higher risk of heart-related mortalities [45].…”
Section: Discussionmentioning
confidence: 81%
“…Rather, available studies focused on diagnosed hypertension while one study that also examined level of awareness of hypertension diagnosis among its participants involved both staff and students. 21,22 There is therefore a need for further studies on prevalence of undiagnosed hypertension among staff of Universities in different regions of Nigeria. Future studies on effective strategies capable of appreciably reducing not only the prevalence of undiagnosed hypertension, but also the prevalence of hypertension among University workforce is also urgently required.…”
Section: Discussionmentioning
confidence: 99%